Zinc finger protein 852 is essential for the proliferation, drug sensitivity, and self‐renewal of gastric cancer cells. (6th January 2022) - Ke, Chao; Zhou, Hongjian; Jiang, Bin; Xie, Xingwang
Abstract: Exploring cellular and molecular mechanisms responsible for gastric cancer growth, survival, self‐renewal, and metastasis helps develop efficacious therapeutic strategies. In this study, the expression and function of zinc finger protein 852 (ZNF852) in human gastric cancer cell lines were characterized. ZNF852 was upregulated in gastric cancer cell lines relative to normal gastric epithelial cell line GES‐1. When the ZNF852 gene was ablated in gastric cancer cell line MGC‐803 using the CRISPR/Cas9‐encoding lentivirus, the proliferation of MGC‐803 was suppressed. ZNF852 deficiency also resulted in the inhibition of MGC‐803 sphere formation, along with decreases in SRY‐box 2 (SOX2), octamer‐binding transcription factor 4 (OCT4), and Nanog homeobox (NANOG), suggesting that ZNF852 sustains self‐renewal of MGC‐803 cells. Furthermore, ZNF852 deficiency increased oxaliplatin‐induced MGC‐803 cell death, implying the role of ZNF852 in drug sensitivity. Subcutaneous infusion of MGC‐803 cells into nude mice illustrated the same effects of ZNF852 on the proliferation and self‐renewal of gastric cancer cells. Similar effects of ANF852 were also seen in gastric cancer cell line SNU‐1. Interestingly, ZNF852 deficiency caused downregulation of epidermal growth factor receptor (EGFR) on gastric cancer cells. In summary, this study uncovers the positive regulatory role of ZNF852 in gastric cancer growth and maintenance. ZNF852 could be a potential therapeutic target for inhibiting gastric cancer initiation or progression.